Soil and environmental issues in sandy soils - Huang, Jingyi; Hartemink, Alfred E. (Earth-science reviews, 2020)
Sandy soils are widely distributed across the world. Due to the growing global population and urbanization, these soils are increasingly used to provide food, feed, fiber, energy, and other services to our society. In this paper, we summarize some recent studies on sandy soils and review the main soil and environmental issues related to the understanding, use, and management. We classify the soil issues into three categories: 1) physical and hydrological, 2) chemical and agronomical, and 3) biological and ecological issues. Recent advances include developing models and methods characterizing soil water repellency, preferential flows, transport of nutrients, agrochemicals and industrial contaminants, and groundwater contamination, soil compaction, erosion and evapotranspiration, improving soil fertility, structure, and biodiversity, monitoring, mapping, and managing salinity, sodicity, carbon sequestration, nutrient cycling, greenhouse gas emission, and heavy metal contamination. The main challenges are to understand changes in sandy soil conditions (e.g. soil water repellency, soil compaction, crust, erosion, salinization, structure, fertility, inorganic and organic contamination) and processes (e.g. evapotranspiration, carbon sequestration, nutrients leaching and cycling, greenhouse gas emission) under intensive agricultural activities and climate change and evaluate the impacts of soil texture on soil properties and processes. A conceptual framework is proposed for holistic understanding and management of sandy soils under changing climate conditions and agricultural activities.